Reduction in hsCRP levels is associated with decreased incidence of cardiovascular events in Japanese hypertensive women but not in men - Kim-Mitsuyama, Shokei (Sci Rep, 2020)
To test our hypothesis that the magnitude of reduction in hsCRP achieved by antihypertensive medications may predict the benefit for cardiovascular outcomes in hypertensive individuals, we performed subanalysis of the ATTEMPT-CVD study. The hypertensive participants enrolled in the ATTMEPT-CVD study were categorized into two groups according to whether achieved reduction in hsCRP levels at 6 months after initiation of antihypertensive medications from baseline was equal to or greater than 40% (responder group) or less than 40% (non-responder group). Baseline characteristics and blood pressure during follow-up period were similar between the groups. For women, the incidence of cardiovascular events was significantly less in responder group than non-responder group (P < 0.0221). However, for men, there was no significant difference between the groups regarding incident cardiovascular events (P = 0.2434). There was a significant interaction (P = 0.0187) between sexes for incident cardiovascular events. Our results provide the evidence suggesting that substantial reduction (40% or greater reduction) in hsCRP on antihypertensive medication predicts the benefit for cardiovascular outcomes in hypertensive women but it does not in hypertensive men. The magnitude of achieved reduction in hsCRP by antihypertensive medications seems to be a useful indicator of successful treatment in Japanese hypertensive women. This trial was registered with ClinicalTrials.gov, number NCT01075698.